You are on page 1of 9

1

* (r ; , ,L) H ( r; , ,L)d
J ( , ,L) =
( r; , ,L)
* (r ; , ,L)J ((,r ;,L) =, ,(rL *
L
; , ),d ) H (r ; , ,L) d


* (r; , ,L) ( r; , ,L)d



J / = J / = L = 0 1


0 0 , ,L

1


( r; , L)

E0 J ( 0 , 0, L),
0 (r ) (r ; 0, 0 ,L)

1







H



H


1
3
4
)
(r;, ,L)
11
15

0* (r ) ( r; , ,L) d = 0




16
18
20

19

9.1 1

n H

= n Cn n 3

= 1 |< 1 | >|2

1
= 1 |< 1 | >|2 = 1 |< 1 | Cn n >|2 = 1 C1*C1

4
1
n


E E1 =< | (H E1 ) | >
E =<1 | H | > = Cn*Cn ( En E1 ) = C2*C2 (E2 E1 ) + C3*C3 (E3 E1 ) + ... +
n

E E1 ( E 2 E1 ) 2 (E2 E1)(C2*C2 + C3*C3 +L)


1

E1 (E2 E1)(1 C1*C1 )


E2 H

6


3
4


-a<x<a



0<x<a

n x
n x n
2
n ( x) = sin 1
1
a a n ( x) = sin ( + ), n = 1, 2,L
h2 2 n2
a 2a 2
En = 2

2 a 2
h 2 2 n 2

0<x<2a

En =
n ( x) =
1
sin
n x
3
8 a 2
a 2a

h2 2 n2
En =
8 a 2 4

9.2
-a <x<a)





x x

= C0 + C2 ( )2 + C4 ( ) 4 + ...,| x |< a 4

a a
( x) = 0,| x | a 1
C2 = C0 ,

x2 15 x2
= C0 [1 ]= [1 2 ] 5

a2 16a a
1 x
1 ( x) = cos , a < x < a 2


a 2a h2
a
d 2 5 h2

2m a dx 2
E= dx =
h 2 2 4 ma 2 6

E1 = = 1.233701h / ma 2 3
8ma 2

E / E1 = 10 / 2 = 1.0132 7

960 E ( )
= 1 |< 1 | >|2 = 1 = 1.445 103 8 = 0

6

4


C = (C + C )
1 = 1.2207500, 2 = 8.317712
4 0 2

x x
( , x) = N [1 + ( ) 2 (1 + )( ) 4 ],| x |< a 9
E ( 1 ) = 1 . 2 3 3 7 1 9 h 2 / m a 2 = 1 .0 0 0 0 1 4 7 E 1 12

a a
E ( 2 ) = 1 2 .7 6 6 3 h 2 / m a 2 13

N


< | >= dx = 1
a
2 E (1 )
E (2 ) E3
a
(1, x)

N 2 a = 315 /16( 2 + 8 + 28) 10
= 1 |< 1 | >|2 = 6.8 107 14


9.1

h2 a d 2 E (1 ) E1 > ( E3 E1 )
E = dx 15

2m a dx2 11


< 1.8 10 6 14

3 11 2 + 36 + 60 h 2
E ( ) = 12

4 2 + 8 + 28 ma 2

2
(1)

N

a
9.4
-a<x<a)



2 dx = 1
a


N 2 = 315 / 16( 2 6 + 21)a 2

( x) = N ( a 2 x 2 )( a 2 x 2 ),| x| < a
0,| x| a (1)
E =
h2

a

d 2
dx 3

2m a dx 2

3 11 2 14 + 35 h 2
E ( ) =

4 2 6 + 21 ma 2 4

E ( )
= 0

1 = 0.2207500, 2 = 7.317712





4
t2 . ..
S = L ( x, x, x, t )dt
2 t1
h
E (1 ) = 1.233719 5

ma 2
h2
E (2 ) = 12.76628 2 6

t2 . ..
ma
S = L( x, x, x, t ) dt
t1

E (1 ) E (2 ) E 3
s
L L . (i ) L .. ( i )
( x
t2
= (i )
xi + .
x + .. ( i )
x ) dt
t1
i =1
x (i )
x

9.2

t

s
L d 2 L d L
S = { [
t2
+ 2 ( . ) ( (i ) )] x}dt
t1 x (i )
dt dt ..
i =1
x (i )
x

L d 2 L d L
[ x i
+
dt 2
( . ) ( ( i ) )] = 0
dt ..
i
x (i )
x
L
L

3
a
1 2
H = T +V = p + kr (2)
2m
9.11 m

Vr= kr , k>0 (1) 1 dV 1
T = r = k r
,(a);b 2 dr 2
Bohr;c 3
E = T + V = k r (3)
2
1 h, m, k
2r 2
(i ) r
(ii ) 1
r0 = ( h / mk ) 3
2
e e 2
(4)

r r0
1
kr0 = ( h 2 k 2 / m ) 3
3 3 (5)
E0
2 2

(b) Bohrr (c) s(l=0)


= (r )
3 (i)
p 2 = mkr , E = kr (6) 3 1
2 ( , r ) = e r , > 0 (9)
2

| r p |= rp = nh, n = 1, 2,3L (7)
h2 h 2 d h2 2
2

T = | |2 d = d =
2m 2m dr 2m
n=1
3k
V = k 0 r 2 4 r 2 dr =
r 2 p 2 = h2 2
2
h 2 3k
6 E ( ) = T + V = + (10)
2m 2
r 2 p 2 = mkr 3 E / = 0 E()
1
r = ( h 2 / mk ) 3 = r0
1 1
3 mk 3 3 3 1
= 2
= (11)
1 2 h 2 r0
E0 = kr0 = ( h 2 k 2 / m ) 3
3 3
(8) 5 1 1
3 h k h2 k 2
2 2 3 3
3
2 2 E = = 1.9656 (12)
2 m m

(ii)
3
1.1.
2 1
2r2
( , r ) = 3
=e 2
, > 0 (13) s(l=0)
4
V ( x) = kx, x > 0

2
h 2 d 3h 2 2 x 0, , ( x) 0
T = d = 1.1
2m dr 4m 1

2k h 2k 2 3
V = k 0 r 2 4 r 2 dr = E0 = 1.8558 (17)
m
3h 2 2 2k (16) E0 0.29%,
E ( ) = T + V = + (14) (12) E05.9%(13)(9)
4m
E / = 0E()
4mk 3 4 3 1
1 1
(13)(9)
= 2
= (15) (13)
3
4
3 h 3 r0 | (0) |2 = = 3 2 r 3 (18)
1 1 0
3h k 2 2
h k
3 2 2 3
(9)
E = 3 = 1.8611 (16) 3
3
4 m m | (0) |2 = = (19)
2 2 r0 3

4
| (0) |2 5.7
m dV 9.15
| (0) |2 = (20)
2 h 2 dr
V (r ) = Ar v , v > 2, Av > 0 (1)
dV / dr = k
mk 1 .(a)
| (0) |2 =
2r 2 / 2
= e (b) e
r / 2
(21) (c)
2 h 2 2 r0 3 .
(18) 8/3(19)3 (a)
(0) 3
1/ 2

(13)(9) ( , r ) = e r / 2 , > 0 (2)


8
h 2 d
2
h2 2
T = d =
2m dr 8m
A
V = 4 A 0 2 r v + 2 dr = v (3 + v )
2
h2 2 A v (3)
E ( ) = T + V = + (3 + v)
8m 2

.
1
(ii) v = 2, A = m 2 .

x e dx = ( ), > 0
+1 x (4) 2
4m
1/ 2
(8)
= 3h
0
E = A(5) 2 A(5)
E / = 0 h
1/(2 + v ) 3h / 2(8)15.5%.
2m
= 2
Av(3 + v ) (5) (iii) v = 1, A > 0,V = Ar ,(6)
h 1/ 3
(3)E() 3 2m
v /(2 + v ) E= A(4) 2 A(4)
A 2m 4 h
E = (2 + v) (3 + v) 2 Av (3 + v) (6)
4 h 3 h A
5/3 2 2 1/ 3
(9)
=
(i) v = 1, A = e .
2
2 m
9.11(12).
A 2m mA2 e2
E= (2) 2 A(2) = 2 = (7) (b)
4 h 2h 2a0
( , r ) = 3/ 2 3/ 4e r
2 2
/2 (10)
a0 = h / meBohr.(7)
2 2

.

h 2 d 3h 2 2
2

T = d = E / = 0
2m dr 4m 1/(2 + v )
4 mA v 3 (12)
= v ( + )
V = 4 A 0 2 r v + 2 dr 3 h
2
2 2
4
= A 3 0 e r r v + 2 dr
2 2
(11),E()
A v 3
v 1 E= (2 + v)( + )
=
2
A e r
v x
+
2 2
dx 2 2
v /(2 + v )

0
2 2m v 3
Av( + ) (13)
2 v 3
3 h
2
= A v ( + ) 2 2
2 2
: (i) v = 1, A = e2 ,.
3h 2 2 2 v 3 4 mA2 4e 2
E ( ) = T + V = + A v ( + ) (11) E= = (14)
4m 2 2 3 h2 3 a0
( E1 = e2 / 2a0 )15.1%.

5
1 (c)(a)(6) Ea (b)
(ii) v = 2, A = m .
2

2
1 (13) Eb
2 5 4 5 m
2 2 2 3 1
E= ( ) m 2 ( ) 2 = h (15)
(2 z ) = 2 2 z 1 1/ 2 z + ( z )
2 3 2 h 2
2
v /( 2 +v )

v /(2 + v )

5 3 3 3 1 1 3 Ea 2 (3 + v)
( ) = ( ) = ( ) = = 3+ v
2 2 2 2 2 2 4 Eb 4 3 ( )
2
2 /(2 + v )
. 2 v / 2 v
= 2 + (17)
(iii) v = 1, A > 0, V = Ar ,(13) 3 2

1 4 mA
1/ 3 1/ 3
3 h A (16)
2 2 1/ 3
v 0, Ea / Eb 1;
E= 3 A(2) (2) = 3
3 h
2
4 m v/2

v 0(v > 2), 2 +


v 2
2 3
9.11(16).
Ea / Eb > 1;

v<0,A>0,
Ea , Eb Ea < Eb ;
v>0,A>0,
Ea , Eb Ea > Eb .

-2<v<0,(a)(b)
v>0,(b)(a).

H

(1) H
( )
(2) H
0 , 1 , 2
, E0 <E1<E2 <
(3)
, = a n n
n

6
H = H d / d

= a n a n` n H n` / an an` nn`
nn nn` ( ) = N (1 + H `) 0
= an En / an
2 2

n n
, H,
, .
0 an / an = E0
2 2

n n 0 0
,

0 H ` 0 = H ` 0 0 H `2 0 = H `2
E0
HamltonH 0, E 0 , 0 , ( )
H , HamiltonH=H 0 + H`
. ( ) ( ) = 1

(4),

(
N = 1/ 1 + 2 H ` 0 +
2 2
H` 2
) 2 H `2 2 ( H ` )2 + 2 H `3
0


E ( ) = E0 + H ` 0 + N 2 2
0 0 0


( ), + H `, [ H 0 , H `] H ` 0 H `2
2

2 0 0

E ( ) = H
H`3 ( , H ` 0 H `2 )
,
= N 2 (1 + H `)( H0 + H `)(1 + H `)
0 0

2
( ) E ( ) = E0 + H ` 0 + 2 H `2 2 ( H ` 0 ) + (
H `, [ H 0 , H `] )
2

= N 2 E0 + H ` 0 + 2 E0 H ` 0 + 2 H `2
0
+ 2 H `H0 H ` 0 + 2 H `3
0
0 2

E / = 0,
2 H `H 0 H `= H `[ H 0 , H `] + H `H 0 + H 0 H `2 [ H 0 , H `] H `
( H` 0 )
2
H `2
1 = 0
H `H 0 H ` 0 = E0 H `2 + H `+ [ H 0 + H `] 1
2 H `, [ H 0 , H `]
2
0 0
0

( H` 0 )
2
H `2
= 0
( ) = N (1 + H `) 0
E0 H `2 0
H `H 0 H ` 0
9.17
(6),E ( )
l2
D COS
H=H 0 + H `=
2 H `2 ( H ` 0 )
2 2

2I
E=E0 + H ` 0 0
H `, [ H 0 , H `]
9.18
H=H 0 + H `= H 0 + e z
0

H `2 ( H ` ) 2 2

h 2 2 e2 p 2 e 2
= E0 + H ` 0 H0 = =
0 0

E0 H ` H `H 0 H ` 0
2
2 r 2 r
0

(1),,
,() 0

7
9.19 8.26
8.26





8.26
8.26
,--
,

h2 2 2
H = ( + ) l2[ (x1) + (x2 )] + l2 (x1 x2 )
2 x12 x22 ,
,Hamilton
Hamilton
x1 , x2 1 , l
12,
1 2 2 1
, , a0 /
,, H = ( 2 + 2 ) (x1) (x2 ) + (x1 x2 )
( a0 Bohr
Bohr), 2l2 / a0 ,
), , 2 x1 x2
= T1 +T2 +V1 +V2 +V12 (1)
1 2 2 1
H = ( 2 + 2 ) (x1) (x2) + (x1 x2)
2 x1 x2
-
-(
()
),
, (, 1, 2 ) = l 1 2
(2)

(
(),
),
.
.

(),H
),H
,
,

2
2
d E ( ) =< H >= 2 2 + (6)
2 dx
< T1 >=< T2 >= l dx = (3) 2
2
2
< V1 >=< V2 >= l ()dx =
(4)


2
2 1 2 2
(1 2 )dx1dx2

< V12 >= l
1
22 41 = 1 (7)
=
0
l dx1 =
2 (5) 4

8

1 2
l / a0
1 2 16
E = (1 ) (8) ,( l )
4

, l2 5
l
2 2
1 l2 1 E= ( )2
E= (1 )2 = ( ) a0 16
a0 4 a0 4 (9)

(9).
(8.26)
l2
E '= ( 2 )
a0 2

:
:

9.21,9.22
9.21,9.22